2013
DOI: 10.1002/smll.201202792
|View full text |Cite
|
Sign up to set email alerts
|

Broad‐Spectrum Antibacterial Activity of Carbon Nanotubes to Human Gut Bacteria

Abstract: Carbon nanotubes (CNTs) hold promise in manufacturing, environmental, and biomedical applications, as well as food and agricultural industries. Previous observations have shown that CNTs have antimicrobial activity; however, the impact of CNTs to human gut microbes has not been investigated. Here, the antibacterial activity of CNTs against the microbes commonly encountered in the human digestion system--L. acidophilus, B. adolescentis, E. coli, E. faecalis, and S. aureus--are evaluated. The bacteria studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(169 citation statements)
references
References 39 publications
7
162
0
Order By: Relevance
“…These negative values of zeta potential of MWCNT dispersions are in consonance with the previous published reports (38,39). Besides the cell-puncturing potential of MWCNTs, increased adhesion of these carbon-based nanoconstructs can be ascribed to the involvement of electrostatic factors too (40). The lower negative charge intensity on MWCNTs might have accounted for reduced repulsion by the negatively surfaced bacterial walls, resulting in relatively better adhesion of the MWCNTs and, thus, improved antibacterial efficacy.…”
Section: Antibacterial Studiessupporting
confidence: 90%
“…These negative values of zeta potential of MWCNT dispersions are in consonance with the previous published reports (38,39). Besides the cell-puncturing potential of MWCNTs, increased adhesion of these carbon-based nanoconstructs can be ascribed to the involvement of electrostatic factors too (40). The lower negative charge intensity on MWCNTs might have accounted for reduced repulsion by the negatively surfaced bacterial walls, resulting in relatively better adhesion of the MWCNTs and, thus, improved antibacterial efficacy.…”
Section: Antibacterial Studiessupporting
confidence: 90%
“…CNTs with a length of more than 50 µm may wrap around the bacterial cell during the antimicrobial activity. 32 Long nanotube aggregates in liquid medium are known to be more bioactive and have potent antibiofilm activity, especially during the early phase of biofilm formation. 33 Carbon nanostructures may cause physical abrasions and structural damage to the bacterial cell walls and cell membranes.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%
“…Several studies including ours have reported that the CNTs possess effectively and broad-spectrally antibacterial activities with the mechanism of killing bacteria by the physical puncture of bacterial membranes, resulting in the damage of the integrity of cell wall and causing the cell death, which suggests for special benefi ts to prevent the growth of multi-drug-resistant microbes. [10][11][12] However, there is still much evidence that CNTs under uncontrolled conditions can cause health risks. A number of studies show that CNT exposure can induce oxidative stress, infl ammatory responses, DNA damage, and so forth.…”
Section: Discussionmentioning
confidence: 98%